Factor XII-Driven Inflammatory Reactions with Implications for Anaphylaxis - Bender, Lysann; Weidmann, Henri; Rose-John, Stefan; Renné, Thomas; Long, Andy T. (Frontiers in Immunology, 2017)
Anaphylaxis is a life-threatening allergic reaction. It is triggered by the release of pro-inflammatory cytokines and mediators from mast cells and basophils in response to immunologic or non-immunologic mechanisms. Mediators that are released upon mast cell activation include the highly sulfated polysaccharide and inorganic polymer heparin and polyphosphate, respectively. Heparin and polyphosphate supply a negative surface for factor XII activation, a serine protease that drives contact system-mediated coagulation and inflammation. Activation of the factor XII substrate plasma kallikrein leads to further activation of zymogen factor XII and triggers the pro-inflammatory kallikrein-kinin system that results in the release of the mediator bradykinin. The severity of anaphylaxis is correlated with the intensity of contact system activation, the magnitude of mast cell activation, and bradykinin formation. The main inhibitor of the complement system, C1 esterase inhibitor, potently interferes with factor XII activity, indicating a meaningful crosslink between complement and kallikrein-kinin systems. Deficiency in a functional C1 esterase inhibitor leads to a severe swelling disorder called hereditary angioedema. The significance of factor XII in these disorders highlights the importance of studying how these processes are integrated and can be therapeutically targeted. In this review, we focus on how factor XII integrates with inflammation and the complement system to cause anaphylaxis and hereditary angioedema as well as highlight current diagnosis and treatments of bradykinin-related diseases.